N6-methyladenine regulator-mediated RNA methylation modification patterns in immune microenvironment regulation of osteoarthritis - Gu, Yong; Wang, Zhengming; Wang, Rui; Yang, Yunshang; Tong, Peijian; Lv, Shuaijie; Xiao, Long; Wang, Zhirong (Frontiers in Genetics, 2023)
Background: Osteoarthritis is a common chronic degenerative disease, and recently, an increasing number of studies have shown that immunity plays an important role in the progression of osteoarthritis, which is exacerbated by local inflammation. The role of N6-methyladenine (m6A) modification in immunity is being explored. However, the role of m6A modification in regulating the immune microenvironment of osteoarthritis remains unknown. In this study, we sought to discuss the association between the N6-methyladenine (m6A) modification and the immune microenvironment of osteoarthritis. Methods: First, the data and gene expression profiles of 139 samples, including 33 healthy samples and 106 osteoarthritis samples, were obtained from the Genetics osteoARthritis and Progression (GARP) study. Then the differences in m6A regulators between healthy individuals and osteoarthritis patients were analyzed. The correlation between m6A regulators and immune characteristics was also investigated by single-sample gene set enrichment analysis (ssGSEA). Principal component analysis (PCA), Gene Set Variation Analysis (GSVA) enrichment analysis, weighted gene coexpression network analysis (WGCNA), and Associated R packages were used to identify the m6A phenotype and its biological functions. Results: A total of 23 m6A regulators were involved in this study. We found a close correlation between most m6A regulators in all samples as well as in osteoarthritis samples. VIRMA and LRPPRC were the most highly correlated m6A regulators and showed a positive correlation, whereas VIRMA and RBM15B were the most negatively correlated. M6A regulators are associated with osteoarthritis immune characteristics. For example, MDSC cell abundance was strongly correlated with RBM15B and HNRNPC. Meanwhile, RBM15B and HNRNPC were important effectors of natural killer cell immune responses. IGFBP3 is an important regulator of cytolytic activity immune function. We performed an unsupervised consensus cluster analysis of the osteoarthritis samples based on the expression of 23 m6A regulators. Three different m6A subtypes of osteoarthritis were identified, including 27 samples in subtype C1, 21 samples in subtype C2, and 58 samples in subtype C3. Different m6A subtypes have unique biological pathways and play different roles in the immune microenvironment of osteoarthritis. Conclusion: The m6A modification plays a crucial role in the diversity and complexity of the immune microenvironment in osteoarthritis.